Banking Competition, Monitoring Incentives and Financial Stability - Thi Quynh Anh Vo (Norges Bank, 2010)
This paper addresses the desirability of competition in banking industry. In a model where banks compete on both deposit and loan markets and where banks can use monitoring technology to control entrepreneurs' behavior, we investigate three questions: what are the effects of competition on banks' monitoring incentives? Does competition hurt banks' stability? What can be devices to correct potential negative effects of competition vis av̀is financial stability? We find that impacts of competition on banks' monitoring incentives can be decomposed into two effects: one on the attractiveness of monitoring and the other on the monitoring efficiency. The first effect operates through the link between competition and loan margin. The second effect comes from the fact that marginal effect of monitoring on entrepreneur's effort depends on loan rate. We characterize the sufficient condition under which competition will increase monitoring incentives as well as banks' stability. For the third question, we focus on the role of capital requirement and claim that with capital requirement, we can attain a weak correction but not strong correction.
hdl:11250/2497447
Keywords: G21; G28; D43; D82; 330